Sustainability transitions in local communities: District heating, water systems and communal housing projects - Jonathan Hugh Köhler; Claudia Hohmann; Elizabeth Dütschke (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
Sustainability transitions take place across geographical and political levels. Services such as energy supply, water supply and wastewater management or housing are part of daily life have to be provided at the district level within larger urban governance structures or by smaller rural administrations. However, relatively little attention has been given to the analysis of these local structures. This paper reviews case studies of niches in the areas of district heat networks, communal housing projects for the elderly and sustainable water/wastewater management. The paper addresses the following research questions: 1. What are the similarities and differences in the case study's drivers and barriers that have arisen between the fields of action and what conclusions can be drawn from these insights in order to maximize success factors or to minimize obstacles in advance? 2. What are the key factors for transition, also with regard to the synergies of the three fields of action? 3. What is the stage of development of the niches? Are they in a transition process or not? District heat networks are established as a niche, but given the current policy and financial environment are developing very slowly. Communal housing projects are a small part of the overall housing market, but the niche is stable and growing. Waste water separation and new rain water management systems are developing as niches, but the centralised management of decentralised waste water treatment has so far only been adopted in a few cases. These niches are all critically dependent on support from the district authorities. High complexity and inconsistency in legal frameworks, and missing financial re-sources present significant barriers for innovative niche projects. They usually require new, specific financial support to enable the change from conventional systems. These groups face a difficult period of developing their expertise in planning and management and often require financial support and advice. Consultancy networks - if available - have been shown to be important in enabling such pro-jects to establish themselves. As all three case studies rely on infrastructure components, stakeholders need to consider windows of opportunities for innovation. Acceptance and trust are additional factors influencing the projects. Therefore, constructive and goal-oriented "interaction" and communication between the stakeholders on district and project level are key factors for success. It is important to share data and information to guarantee an early integration of important stakeholders, including the public. Projects in all three areas have the ambition of improved sustainability, although data on the actual impact is limited. The housing projects can be argued to contribute to sustainability in all three areas: environmental, social and economic. The district heat networks are supposed to reduce environmental impacts compared to current systems, but there was insufficient monitoring information to be certain that this is the case. The alternative water management systems all make a contribution to environmental sustainability and can be shown to be economically viable. If successful, projects in all three sectors can strengthen local social structures. Economic sustainability is a necessary condition for the success of projects in all three areas and this requires financial support and resources that are not available through the conventional housing, energy or water services market institutions. While projects on district and household level are fundamental to a sustainability transition, efforts for upscaling their impacts (Luederitz et al. 2017) are just as important. The challenges for actors on local to global scale are to learn from different narratives and adapt different perspectives, build unconventional alliances and collaborations to implement innovative, creative and intelligent solutions for a sustainability transition on a larger scale (Luederitz et al. 2017; Wittmayer et al. 2016; Brown et al. 2013).
urn:nbn:de:0011-n-5199232; Additional information: Werkstattbericht Nr. 9 in the TRANSNIK project - This work was funded by the BMBF (German Federal Ministry of Education and Research) through the TRANSNIK project (funding reference 01UT1417A-C).
Keywords: 330